Problem nadużywania uprawnień przez funkcjonariuszy służb porządkowych w Turcji od roku 2005 po wydarzenia w stambulskim Parku Gezi - Radziej, Katarzyna (Refleksje. Pismo naukowe studentów i doktorantów WNPiD UAM, 2015)
This article is a description of excessive use of force by the law enforcement in Turkey, legislative changes in this area and their implications since the beginning of Turkish EU accession bid. First part of the article focuses on the process of law and police proceedings adjustment to the EU’s norms. This problem is mainly described by law enforcement faulty actions. Second part of the article depicts Gezi Park protests as an example of described abuses.